PbS Nanowires-on-Paper Sensors for Room-Temperature Gas Detection - Kan, Hao; Li, Min; Luo, Jingting; Zhang, Baohui; Liu, Jingyao; Hu, Zhixiang; Zhang, Guangzu; Jiang, Shenglin; Liu, Huan (IEEE sensors journal, 2019)
Paper-based gas sensors represent an emerging important class of devices in flexible electronics. Colloidal nanocrystals unite large surface-to-volume ratio with excellent solution processability, offering avenues to high-performance paper-based gas sensors. One of the factors limiting the performance of paper-based gas sensors is the sphere-like morphology of semiconductor nanocrystals, making it difficult to construct a stable sensing network to ensure efficient carrier transport and mechanical robustness. Here we demonstrated sensitive and flexible gas sensor via the spray coating of PbS nanowires onto paper substrates at room temperature. The pencil-drawn graphite electrode was employed to simplify the sensor design and fabrication. Unlike the sphere-like PbS nanocrystals that usually assemble into compact thin-film solids, the PbS nanowires-on-paper sensor exhibits a porous network microstructure, which not only offers efficient pathway for gas adsorption and diffusion but also possesses inherent flexibility for superior mechanical bendability. The response of the PbS nanowires-on-paper sensor toward 50 ppm of NO 2 at room temperature was 17.5, with the response and recovery time being 3 and 148 s, respectively. The sensor shows only a slight decrease in response (6% of the initial value) and identical temporal response when subject to 500 bending and unbending cycles. The competitive adsorption of NO 2 with O 2 on PbS surfaces is proposed as the sensing mechanism accounts for the high sensitivity and good reversibility at room temperature. Our results highlight the significance of the solution-processable nanowires as the ideal building blocks for the flexible paper-based gas sensors.